A semiotic analysis of consumer-generated antibranding - Kucuk, S. Umit (Marketing Theory, 2015)
This study is a semiotic analysis of consumer-generated antibranding efforts and reveals tacit semiotic rules used by digital antibranders. A broad theoretical discussion about the semiotic characteristics of branding and antibranding is provided and “digital antibranding semiotics” is defined. The semiotics of consumer digital antibranding efforts are investigated in two studies examining a sample of antibranding images targeted at valuable corporate brands. The first study reveals that antibranders use drama and humor to demonize, criminalize, dehumanize, and “Hitlerize” the targeted brands, creating strong antibrand voices and positioning themselves against corporate greed and wrongdoing. The second study found that consumers successfully decode antibranding semiotic representations and classify them in terms of message clarity, fact finding, and “hostility versus entertainment values.” These findings reveal that both antibranding images with dark humor and clear messages and an aggressive and intriguing message have the potential to influence consumers.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDcwNTkzMTE0NTQwNjc3